Pain-Free Alpha-Synuclein Detection by Low-Cost Hierarchical Nanowire Based Electrode - Gisella M. Di Mari; Mario Scuderi; Giuseppe Lanza; Maria Grazia Salluzzo; Michele Salemi; Filippo Caraci; Elena Bruno; Vincenzina Strano; Salvo Mirabella; Antonino Scandurra (Nanomaterials, 2024)
Analytical methods for the early detection of the neurodegenerative biomarker for Parkinson’s disease (PD), α-synuclein, are time-consuming and invasive, and require skilled personnel and sophisticated and expensive equipment. Thus, a pain-free, prompt and simple α-synuclein biosensor for detection in plasma is highly demanded. In this paper, an α-synuclein electrochemical biosensor based on hierarchical polyglutamic acid/ZnO nanowires decorated by gold nanoparticles, assembled as nanostars (NSs), for the determination of α-synuclein in human plasma is proposed. ZnO NSs were prepared by chemical bath deposition (CBD) and decorated with electrodeposited Au nanoparticles (Au NPs). Then, electro-polymerized glutamic acid was grown and functionalized with anti-α-synuclein. A synergistic enhancement of electrode sensitivity was observed when Au NPs were embedded into ZnO NSs. The analytical performance of the biosensor was evaluated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), using the Fe(II)(CN)64−/Fe(III)(CN)63− probe. The charge transfer resistance after α-synuclein recognition was found to be linear, with a concentration in the range of 0.5 pg·mL−1 to 10 pg·mL−1, a limit of detection of 0.08 pg·mL−1, and good reproducibility (5% variation) and stability (90%). The biosensor was also shown to reliably discriminate between healthy plasma and PD plasma. These results suggest that the proposed biosensor provides a rapid, quantitative and high-sensitivity result of the α-synuclein content in plasma, and represents a feasible tool capable of accelerating the early and non-invasive identification of Parkinson’s disease.